USING COOPERATIVE MIND MAPPING SUMMARY STRATEGY TO IMPROVE THE READING COMPREHENSION SKILL OF PUBLIC ADMINISTRATION STUDENTS’ IN UNISBA BLITAR - Nuryanti , Nuryanti (Universitas Islam Balitar, 2020)
This research was purposed to determine that cooperative mind mapping summary strategy can improve reading comprehension skill of Public Administration Students’. The research conducted in Public Administration of UnisbaBlitar in 2019 - 2020. The respondents were 30 students. The researcher conducted research using Classroom Action Research (CAR) and individual research design. The procedures of research were preliminary study, plan the action, implementing the plan, observation, and reflection. The data collections are through observation, questionnaire, field note, and test.The research result showed that Cooperative Mind Mapping Summary Strategy could increasethe reading comprehension skill of Public Administration Students’.